#TITLE_ALTERNATIVE# - ANGGA UTAMA (NIM : 22114044), IVAN
In underground mining activities, the opening excavation should be made. So it affect to rock mass stress condition around opening excavation that can make instability around opening excavation. Physical model and numerical model are conducted to study the stress distribution. In this research, physical model is conducted using photoelastic method. From photoelastic method, the value of principal stress can be obtained. This photoelastic method is applied in the biaxial test with various forms of tunnel openings. Sample testing conducted at the Laboratory of Geomechanics and Mine Equipment Institute of Technology Bandung involved the physical properties test and mechanical properties test to obtain the sample characteristics as input data for numerical modeling using RS3 2.0, such as the natural density, uniaxial compressive strength, Young’s modulus, Poisson’s ratio, and tensile strength. From biaxial test using photoealstic method, the color pattern will be obtained for calculating the stress following stress optic equation. The value of the principal stress from photoelastic method will be compared with the value of the principal stress from numerical method. From the results of this study, the largest error of 52,54% at the multiple horseshoe excavation and the smallest error of 0,83% at the single circular excavation.